Penerapan Kebijakan Keringanan Kredit Selama Masa Pandemi Covid-19 di Kota Jayapura - Theresia Hilda Krey (Universitas Cenderawasih, 2022)
The COVID-19 pandemic that has plagued the world since the end of 2019 in Wuhan Province of China, finally spread to Indonesia in early March 2020. The economic sector is the sector most affected by this pandemic. One of the efforts made by the government to stop the spread of COVID-19 is by limiting operating hours for entrepreneurs. Of course it has negative impacts on economic sector in Jayapura City, including material losses and decreased income, especially entrepreneurs who have loans with guarantees for their businesses to operate. In the midst of economic difficulties, the Indonesian government through the Financial Services Authority issued a policy named the Financial Services Authority Regulation Number 11 of 2020 concerning National Economic Stimulus as a Countercyclical Policy for the Impact of the Spread.of Coronavirus Disease 2019.This study aims to determine the extent to which the policy is implemented in Jayapura City and the various obstacles encountered during the process of implementing the policy. The research method used is a normative and empirical legal approach.As a result, the POJK No.11/POJK.03/2020 policy has apparently been implemented in several financial institutions in Jayapura City, but there are still many obstacles encountered during the implementation of this policy so that wider socialization is needed so that the public can get information related to the policy.